Examination Of The Ruling Of The Syar'iyah Court On Divorce Cases Lawsuit - Abdullah, Asnawi; Toguan, Zulfikri; Syahrul, Fatahillah; Saleh, Muhammad (Journal of Mujaddid Nusantara, 2024)
When there is an indication of judicial negligence in providing legal considerations, it is highly possible to conduct an examination or investigation. The decision of the Bireuen Sharia Court regarding divorce on demand, the panel of judges pronounced talak ba’in sughrā against the plaintiff without first attempting reconciliation through the appointment of an arbitrator. Looking at the legal provisions, when a case falls under shiqāq, the judge must appoint an arbitrator. Therefore, departing from this issue, there is a need for an examination as to why the judge did not appoint an arbitrator to resolve the dispute and what legal considerations were provided by the judge. This study is designed with a qualitative pattern, utilizing a statutory approach. Data collection techniques involve documentation and interviews. The research findings prove that the panel of judges argued that it did not fall under shiqāq cases, hence the appointment of an arbitrator was not necessary. The legal considerations provided by the judge in the divorce ruling include fiqhiyah principles, legal provisions, Supreme Court jurisprudence, Quranic verse al-Rūm ayat 21, and fiqhiyah principles.